Eczema with secondary impetigo and double lymphangitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Lymphatic vessels and lymph nodes represent a second level defense system of the organism able to prevent the generalized diffusion in the organism of harmful agents such as bacteria or larvae of arthropods: when agents of this type affect the skin and the local defense system is not able to stem their spread, these agents penetrate into lymphatics and reach the lymph nodes; in the lymphatics they damage the endothelial wall up to obliteration. These disorders manifest themselves clinically as flushed, painful striae that from the lesion are directed towards the lymph nodes (2). The most frequent cause of lymphangitis is filariasis, but also other infestations such as furuncular myiasis (1) may be liable for lymphangitis. Lymphangitis of the limbs is also observed during primary or secondary infections to itchy dermatitis, scabies or eczema, as in our case which is peculiar for the presence of two lymphangitis striae.